Trigeminal Neuralgia Secondary to Meningiomas and Vestibular Schwannoma Is Improved after Stereotactic Radiosurgery: A Systematic Review and Meta-Analysis - Peciu-Florianu, Iulia; Régis, Jean; Levivier, Marc; Dedeciusova, Michaela; Reyns, Nicolas; Tuleasca, Constantin (Stereotactic and functional neurosurgery, 2021)
INTRODUCTION: Trigeminal neuralgia (TN) secondary to tumors is encountered in up to 6% of patients with facial pain syndromes and is considered to be associated with tumors affecting the trigeminal nerve pathways. The most frequent are meningiomas and vestibular schwannomas (VS). Stereotactic radiosurgery (SRS) has emerged as a valuable treatment, with heterogeneity of clinical results. We sought to review the medical literature on TN treated with SRS for meningiomas and VS and investigate the rates of improvement of TN symptoms. METHODS: We reviewed articles published between January 1990 and December 2019 in PubMed. Pain relief after SRS, the maintenance of pain relief, and TN recurrence and complications were evaluated with separate meta-analyses, taking into account the data on individual patients. RESULTS: Pain relief after SRS was reported as Barrow Neurological Institute (BNI) pain intensity scores of BNI I in 50.5% (range 36-65.1%) of patients and BNI I-IIIb in 83.8% (range 77.8-89.8%). There was no significant difference in series discussing outcomes for tumor targeting versus tumor and nerve targeting. Recurrences were described in 34.7% (range 21.7-47.6; tumor targeting). Maintenance of BNI I was reported in 36.4% (range 20.1-52.7) and BNI I-IIIb in 41.2% (range 29.8-52.7; tumor targeting series). When both the nerve and the tumor were targeted, only 1 series reported 86.7% with BNI I-IIIb at last follow-up. Complications were encountered in 12.6% (range 6.3-18.8; tumor targeting series) of patients; however, they were much higher, as high as 26.7%, in the only study reporting them after targeting both the nerve and the tumor. The most common complication was facial numbness. CONCLUSION: SRS for TNB secondary to benign tumors, such as meningiomas and VS, is associated with favorable clinical course, but less favorable than in idiopathic TN. There was, however, heterogeneity among reports and targeting approaches. Although targeting both the nerve and the tumor seemed to achieve better long-term results, the rate of complications was much higher and the number of patients treated was limited. Future clinical studies should focus on the standard reporting of clinical outcomes and randomization of targeting methods.
Keywords: Meningeal Neoplasms; Humans; Meningioma; Vestibular schwannoma; výsledek terapie; Trigeminal neuralgia; lidé; neuralgie trigeminu; Stereotactic radiosurgery; radiochirurgie; Neuroma, Acoustic; Radiosurgery; vestibulární schwannom; Retrospective Studies; Treatment Outcome; Pain Management; Trigeminal Neuralgia; Gamma knife surgery; retrospektivní studie; meningeom; management bolesti; meningeální nádory